Daya Terima Dan Kadar Zat Besi (Fe) Serundeng Ampas Kelapa - Amiroh Amiroh; Armita Athennia; Desi Ramayanti (Fakultas Ilmu Kesehatan Universitas Gresik, 2023)
Coconut pulp is a by-product of coconut milk processing. Coconut pulp is known to have a high iron content so that its potential to be food iron sources. Serundeng is a complementary food used in the community. The purpose of this study was to determine the effect of coconut substitution by coconut pulp on the organoleptic properties and acceptabilities as well as the increasing in iron (Fe) levels. This study was experimental with 5 treatments, P1 (0 gr of coconut pulp), P2 (25 gr of coconut pulp), P3 (50 gr of coconut pulp), P4 (75 gr of coconut pulp), P5 (100 gr of coconut pulp). This study used the ANOVA test and continued with DMRT when there was a significant influence. The results of the hedonic quality test showed that there was an influence of coconut pulp substitution on aspects of color, compactness, taste and aroma. On hedonic tests it is known that there was no significant influence. The iron content of coconut pulp (P5) is 2.75 mg / 100g. There was an increase in iron content by 27% when compared to pure coconut group.